Open Photonics: An integrated approach for building a 3D-printed motorized rotation stage system - Yannic Toschke; Jan Klenen; Mirco Imlau (HardwareX)
In the context of experimental optics- and photonics-research, motorized, high-precision rotation stages are an integral part of almost every laboratory setup. Nevertheless, their availability in the laboratory is limited due to the relatively high acquisition costs in the range of several 1000€ and is often supplemented by manual rotation stages. If only a single sample is to be analyzed repeatedly at two different angles or the polarization of a laser source is to be rotated, this approach is understandable. Yet, in the context of automation and the associated gain in measurement time, cost-effective and precise rotation stages designed for the use of optics are lacking.We present a low-cost alternative of a motorized high precision rotation stage system. The design is based on a combination of 3D-printed components, which form the monolithic mechanical framework, and a stepper motor controlled by an ESP32 based microcontroller. By coupling the motor and rotation unit via a toothed belt, backlash is minimized and at the same time high positioning accuracy can be achieved. Finally, the implementation of remote procedure calls for serial communication and the utilization of a physical home switch and incremental encoder complete the desired feature set of an integrated system for laboratory setups. The total costs can thus be reduced to less than 100€ without significantly restricting the performance criteria.